Why do female audiences subscribe to these types of streamers? An empirical study on the motivations of Chinese Huya users - Wang, Sijun (Frontiers in Psychology, 2023)
Abstract：Chinese live-streaming economy is in accelerated pace among young audiences, whereas the motivations underlying female users lack academic researches. Adopting a mixed approach, this study applies Uses and Gratification Theory to explain the subscription behaviour based on Chinese live-streaming platform Huya. Through Research data collected from online communities (n = 202), female audiences' preference about the streamers has been revealed. Findings show that speech style, humour and streaming quality are the most prominent attributes; while some results are against previous studies with predominantly male participation such as excellent mastery of skills and physical appearance and voice. Theoretical and methodological implications of these findings and this approach are discussed. Accordingly, the research gives recommendations to streamers and live streaming platforms for user growth and maintenance.